Neutralizing antibodies for poliovirus in newborn children sera before and after mass immunization of Brazilian population from one to five years old, São Paulo Brazil, 1980 - Hutzler, Rudolf Uri; Fujita, Mitiko; Waldman, Eliseu Alves; Ayub, Munir A.; Ferrari, Flávio L.; Pinto, Paulo R. P.; Cury, Paulo Cesar; Kim, Jai S.; Matheus, José Guido (Revista do Instituto de Medicina Tropical de São Paulo, 1984)
Blood samples from 178 new-born children in the nurseries of hospital located in São Paulo Municipality were examined. The samples from 90 children were obtained before "The First National Day For Poliomyelitis Vaccination" and 88 were analysed after "The Second National Day For Poliomyelitis Vaccination", both of them achieved in 1980. During these vaccination campaigns, it was observed that the number of children susceptible for three poliovirus serotypes decreased from 8.9% to 4.5%; on the other hand, there was an increase in immunized children for the three serotypes from 38.9% to 52.3%. These differences were statis- tically significative at level of 5.0%. After mass immunization, an increase in relation to the neutralizing antibodies titres against polioviruses was observed in newborns, who presented titres equal or higher than 8. The proportion of children turned from 68.9% to 81.8%, from 73.3% to 83.0% and from 57.8% to 70.5%, respectively for serotypes 1, 2 e 3. These differences were statistically significative, at level of 5.0%, concerning to polioviruses 1 and 3.